Childhood Poisoning, A Rising Epidemic in Developing Nations: Large Single Centre Study - Mishra, Shubhankar; Ramkumar, T.V.; Biswas, Ashok Kumar; Panigrahi, Sambedana (Journal of Nepal Paediatric Society, 2018)
Introduction: Poisoning is a major problem in children. The aims of this study were to determine the pattern of poisoning in children along with seasonal incidence, duration of treatment and outcome in referral centre of eastern India. Materials and Methods: All the children admitted to paediatric ward of MKCG Medical college and hospital from 1st April 2015 to 31st March 2016 (1 year) with history or suspicion of poisoning and animal bites were included in the study. Brought dead patients and the children with side effects due to ingested drugs in prescribed amount were excluded from the study. Results: Total 530 cases were documented with highest incidence in rainy season. 1-6 years children were mostly vulnerable (42.6%). Accidental mode was the major cause in small children and suicidal, in older. Animal bites and stings (n=241) were the commonest followed by chemical poisonings. Kraits were commonest culprit in snake envenomation group. Alprazolam was most common drug causing drug overdose. Total numbers of death were 27. Major cause of death was organo- phosphorus poisoning (OP) and snakebite. Mean days of hospitalization was 2.5 days and death after hospitalization was 1.8 days. Conclusion: Most of the childhood poisonings were due to accidental cause. Animal bites were mostly due to snakes. Maximum numbers of deaths were due to OP poisoning. Watchful observation, clean and clear environment, understanding the problems of adolescence, friendly atmosphere in home can prevent most of the poisonings and animal bites in children.